2018
DOI: 10.1177/0363546517743969
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Subsurface Changes to Magnetic Resonance Imaging UTE-T2* 2 Years After Anterior Cruciate Ligament Reconstruction Correlate With Walking Mechanics Associated With Knee Osteoarthritis

Abstract: Elevated deep UTE-T2* values of medial knee cartilage 2 years after ACLR correlate with 2 clinical markers of increased risk of medial knee OA. These results support the clinical utility of MRI UTE-T2* for early diagnosis of subsurface cartilage abnormalities. Longitudinal follow-up of larger cohorts is needed to determine the predictive and staging potential of UTE-T2* for posttraumatic OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 37 publications
9
92
1
1
Order By: Relevance
“…Compared to an earlier longitudinal study in which initially elevated UTE‐T2* values in ACLR subjects resolved over 2 years to control levels in ACLR subjects without concomitant meniscus tears, this cross‐sectional study of subjects 2 years after ACLR suggests that elevated UTE‐T2* values persist in roughly half of all ACLR subjects including among ACLR subjects without evidence of structural damage to the articular cartilage or menisci by morphological MRI. Recent work by Titchenal et al, examining a subset of ACLR subjects included in the current study, found associations between elevated UTE‐T2* and mechanical markers of higher medial knee OA risk . Specifically, UTE‐T2* values in deep medial tibial cartilage correlated to knee adduction moment and mechanical axis with higher medial knee UTE‐T2* values seen in knees with varus alignment and greater knee adduction moments .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Compared to an earlier longitudinal study in which initially elevated UTE‐T2* values in ACLR subjects resolved over 2 years to control levels in ACLR subjects without concomitant meniscus tears, this cross‐sectional study of subjects 2 years after ACLR suggests that elevated UTE‐T2* values persist in roughly half of all ACLR subjects including among ACLR subjects without evidence of structural damage to the articular cartilage or menisci by morphological MRI. Recent work by Titchenal et al, examining a subset of ACLR subjects included in the current study, found associations between elevated UTE‐T2* and mechanical markers of higher medial knee OA risk . Specifically, UTE‐T2* values in deep medial tibial cartilage correlated to knee adduction moment and mechanical axis with higher medial knee UTE‐T2* values seen in knees with varus alignment and greater knee adduction moments .…”
Section: Discussionsupporting
confidence: 50%
“…The goal of the current work is to probe these provocative findings more thoroughly with a Level I diagnostic study employing a 3‐D measure of MRI UTE‐T2* maps encompassing more cartilage, in medial tibiofemoral regions of known thinning with osteoarthritis 11 , and in a larger cohort of ACLR subjects. The purpose of this study is to (1) examine the relative utility of a larger but more processing‐intensive 3‐D assessment of UTE‐T2* maps compared to the smaller but less processing‐intensive 2‐D assessment and (2) examine a 3‐D assessment of UTE‐T2* maps for evidence of alterations to the medial tibiofemoral subsurface cartilage matrix that has been shown to correlate with mechanical markers of increased medial knee OA risk in human subjects 2 years after ACLR …”
mentioning
confidence: 99%
“…The UTE‐T 2 * measurements of cartilage reflect matrix architecture of articular cartilage and can be an important marker of progressive cartilage degeneration . While UTE‐T 2 * values are decreased in the setting of severe degenerative changes, elevated UTE‐T 2 * values observed after acute trauma have been associated with persistent and irreversible cartilage damage . These various quantitative imaging sequences may allow for earlier detection of cartilage degeneration than traditional radiography and provide a method for precisely following the effects of treatment on cartilage health.…”
Section: Pre‐structural Imagingmentioning
confidence: 99%
“…Ithurburn et al reported that lower two‐year post‐operative activity levels after ACL reconstruction were associated with evidence of cartilage degeneration at 5 years after ACL reconstruction as measured by T 1 ρ and T 2 mapping. Abnormal walking mechanics have been correlated with elevated UTE‐T 2 * measurements in patients after ACL reconstruction, with increased knee adduction moments observed in patients with abnormal deep cartilage UTE‐T 2 * values . T 2 mapping has also allowed for the detection of early cartilage degeneration following partial meniscectomy relative to patients undergoing meniscal repair, highlighting the ability for this measurement to evaluate changes in the cartilage after treatment for meniscus pathology .…”
Section: Pre‐structural Imagingmentioning
confidence: 99%
See 1 more Smart Citation